Dilation versus laser resection in subglottic stenosis: protocol for a prospective international multicentre randomised controlled trial (AERATE trial). Issue 3 (17th March 2022) - Soumagne, Thibaud; Guibert, Nicolas; Atallah, Ihab; Lacasse, Yves; Dutau, Hervé; Fortin, Marc
Abstract : Introduction: Subglottic stenosis (SGS) is a rare condition that results from progressive narrowing of the upper airways. Outcomes and treatment options depend on the benign or complex nature of the stenosis. Treatment options for SGS include surgery and endoscopic techniques. The main endoscopic techniques used are dilation and laser resection. Observational and retrospective studies suggest that endoscopic laser resection may be more effective than dilation. We, therefore, aimed to compare the effectiveness of dilation and laser resection in preventing recurrence of SGS. Methods and analysis: AERATE (dilAtion vs laser Endoscopic Resection in subglottic trAcheal sTEnosis) is a multicentre, investigator-initiated, randomised controlled trial, comparing endoscopic dilation to endoscopic laser resection for simple benign SGS (less than 1 cm long without underlying cartilaginous damage) referred for endoscopic treatment (first treatment or recurrence). The study will be conducted in three centres in France and one in Canada with other centres from France and Canada expected to join. The primary outcome is the recurrence rate of stenosis at 2 years. Recurrence is defined as having a new onset of symptoms along with a stenosis of more than 40% (confirmed by bronchoscopy) requiring a new procedure. A sample size of 100 patients is calculated for the primary endpoint assuming a 10% recurrence rate in the laser resection group and 33% in the dilation group with a statistical significance level of 5%, a power of 80%. Ethics and dissemination: This study is approved by local and national ethics committees as required. Results will be published, and trial data will be made available. Trial registration number: NCT04719845 .